2020
DOI: 10.1097/jpn.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Very Low-Birth-Weight Infant's Intestinal Microbiome

Abstract: The intestinal microbiome is the genetic material from microorganisms residing in the intestinal tract. Very low-birth-weight infants (VLBW; birth weight ≤1500 g) are a physiologically compromised population undergoing a unique period of initial intestinal microbiome establishment. Evidence supports a connection between the intestinal microbiome and gastrointestinal illness that disproportionately affects VLBW infants. Necrotizing enterocolitis, an inflammatory and often necrotic condition of the intestine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…Meanwhile, the limitation is that because this is a cross-sectional study, the authors cannot confirm a temporal relationship between exposure and outcome variables. Another limitation is that it did not investigate some of the known risk factors from previous studies for LBW, including dietary and nutritional factors 42,43 , genetic factors, and [44][45][46] , as well as pollution and environmental factors 47,48 . This limitation is more due to limited secondary data from the 2017 IDHS.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Meanwhile, the limitation is that because this is a cross-sectional study, the authors cannot confirm a temporal relationship between exposure and outcome variables. Another limitation is that it did not investigate some of the known risk factors from previous studies for LBW, including dietary and nutritional factors 42,43 , genetic factors, and [44][45][46] , as well as pollution and environmental factors 47,48 . This limitation is more due to limited secondary data from the 2017 IDHS.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Feeding of predominantly MOM increased intestinal microbial diversity compared with DHM, and even small quantities of MOM were associated with a more favorable microbial community in all but one of the studies. 30,31,36,38 Although Parra-Llorca et al 32 were unable to detect differences in microbial diversity and richness, they concluded that feeding type significantly influenced the preterm intestinal microbial composition, with infants fed MOM showing a significant greater presence of nonpathogenic bacteria. In contrast, a higher abundance of potentially pathogenic bacterial was identified in infants fed DHM.…”
Section: Discussionmentioning
confidence: 99%
“…Spread to the amnion could be either hematogenous via transient bacteremia. TNF-a and interleukin-6 (IL-6) have been shown to cross human fetal membranes in an in vitro culture study[ 26 27 ] Although it is difficult to extrapolate these results to the in vivo situation, it is plausible that infections remote from the genitourinary tract such as in periodontal disease could influence the fetal-placental unit.…”
Section: Discussionmentioning
confidence: 99%